Language Variation in Lexical Variables of Madurese Terms of Address Used by Youths in Bondowoso Regency: A Sociolinguistic Investigation - Alfi Hidayatu Miqawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study attempts to investigate the usage of address terms among youths (university students) across a range of situations in Bondowoso. A qualitative method with an ethnographic approach was deployed. Fifteen most representative students were taken as the source of data. The data were obtained through participatory and non-participatory observation interviews, and a questionnaire. The findings show that the students employ different terms of address, both when they address people and when they address themselves for others. The ways of addressing other people used are based on their age, social or educational status, and or their kinship relationship. The terms to address others and to address themselves for others are classified into four levels; the least polite, polite, more polite, and the most polite. They use be’na or be’en, sampeyan/sampiyan, panjenengan, ajunan to address others and engkok/sengkok, kaule, dhalem, and abdina to address themselves to others. In addition, the lexical variation occuring when they address people using the least polite way is based on their geographical distribution. From the findings, it can be concluded that politeness strategy in terms of address among youths in Bondowoso exists and its implementation varies depending on their interlocutors (social) and the subdistricts where they live (geographical. Keywords: terms of address, politeness strategy, youths, Madurese language